2023
DOI: 10.3390/polym15122716
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Critical Issues in High-Speed Vat Photopolymerization

Abstract: Vat photopolymerization (VPP) is an effective additive manufacturing (AM) process known for its high dimensional accuracy and excellent surface finish. It employs vector scanning and mask projection techniques to cure photopolymer resin at a specific wavelength. Among the mask projection methods, digital light processing (DLP) and liquid crystal display (LCD) VPP have gained significant popularity in various industries. To upgrade DLP and LCC VPP into a high-speed process, increasing both the printing speed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 123 publications
0
8
0
Order By: Relevance
“…In this research, the impact of different curing time on the fabrication process was evaluated, and the designed MNs patches were printed at 0° angle using three different curing times: 1.0, 1.5 and 2.0 s. Interestingly, the results showed that a curing time of 1.0 s was insufficient for curing the 3D-printed MNs patches because all shapes of the needle (shape A, B, C and D) were not able to print. Because of the low curing time, the polymer resin cannot be cured properly 28 resulting in low adhesion to the movable platform 12 . Consequently, the cured resin strongly attached to the FEP film instead of the movable platform (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this research, the impact of different curing time on the fabrication process was evaluated, and the designed MNs patches were printed at 0° angle using three different curing times: 1.0, 1.5 and 2.0 s. Interestingly, the results showed that a curing time of 1.0 s was insufficient for curing the 3D-printed MNs patches because all shapes of the needle (shape A, B, C and D) were not able to print. Because of the low curing time, the polymer resin cannot be cured properly 28 resulting in low adhesion to the movable platform 12 . Consequently, the cured resin strongly attached to the FEP film instead of the movable platform (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2 b) leading to printing failures. To ensure strong adhesion to the movable platform and previous cured layers, a longer curing time is necessary to overcome the separation force 28 . However, an excessive curing time can damage the surface of the 3D-printed object and makes the 3D-printed model inaccurate 15 , 28 .…”
Section: Resultsmentioning
confidence: 99%
“…A notable difficulty of MIP-VPP processes is the presence of rough surfaces [18], primarily originating from two aspects: layer stepping and pixelated aliasing [19]. Layer stepping arises when a set of 2.5-dimensional layers is employed to approximate a three-dimensional (3D) model, resulting in a 'staircase' effect on the surface in the Z-direction [20].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, as the laser needs to eventually move and trace the entire volume of the object being printed pixel by pixel, SLA is relatively slow. Mask projection VPP techniques such as those that employ a digital light projector (DLP) (Figure 2) or a liquid crystal display (LCD) instead expose an entire layer of resin to light at a time, masking the areas which do not need to be cured [26]. The continuous light interface production (CLIP) technique uses a more advanced projector and a polymerization-inhibiting oxygen layer above the base of the vat, and it allows for continuous printing at speeds up to a hundred times higher than SLA or DLP [23].…”
Section: Introductionmentioning
confidence: 99%